1013. TANACETUM DENSUM subsp. AMANI. (23rd January 2022) - Hind, Nicholas; Strange, Kit; King, Christabel
Summary: Tanacetum densum (Labill.) Sch.Bip. subsp. amani Heywood (Compositae: Anthemideae: Anthemidinae) is illustrated and described. Notes on cultivation, propagation, pests and diseases and availability are provided. The position of Tanacetum in the tribe Anthemideae is discussed, as well as the size of the genus, and previous treatment of many of the species in Pyrethrum . The homonymy of Pyrethrum Zinn is outlined, and the likely position of P. bidens Medik. is discussed: a position in either Acmella or Spilanthes, in the tribe Heliantheae, is proposed. The phytochemistry of Tanacetum densum subsp. amani is discussed.